2021
DOI: 10.1111/jth.15256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender‐affirming hormone use on coagulation profiles in transmen and transwomen

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 46 publications
3
33
0
1
Order By: Relevance
“…In accordance, the incidence of VTE was increased in transgender women with 2-and 8-year risk differences of 4.1 (95% CI, 1.6-6.7) and 16.7 (6.4-27.5) per 1000 persons relative to cisgender men and 3.4 (1.1-5.6) and 13.7 (4.1-22.7) relative to cisgender women (88). Measurement of coagulation markers confirmed procoagulant changes during the initiation of GAHT (89).…”
Section: Venous Thromboembolism (Vte)mentioning
confidence: 70%
See 1 more Smart Citation
“…In accordance, the incidence of VTE was increased in transgender women with 2-and 8-year risk differences of 4.1 (95% CI, 1.6-6.7) and 16.7 (6.4-27.5) per 1000 persons relative to cisgender men and 3.4 (1.1-5.6) and 13.7 (4.1-22.7) relative to cisgender women (88). Measurement of coagulation markers confirmed procoagulant changes during the initiation of GAHT (89).…”
Section: Venous Thromboembolism (Vte)mentioning
confidence: 70%
“…Other risk factors for VTE include BMI > 25 kg/m 2 , genetic factors and previous VTE (90,91). The route of estrogen administration affects the risk of VTE (89,91). Oral E2 changes hemostatic variables in a pro-thrombotic direction in contrast to transdermal E2, which was similar to placebo in a recent meta-analysis (91).…”
Section: Venous Thromboembolism (Vte)mentioning
confidence: 99%
“…The concentration of the coagulation marker fibrinogen transiently increased after 3 months of transdermal estradiol combined with CPA. Similarly, a recent study on the effect of GAHT on coagulation parameters observed more procoagulant profiles in trans women [ 33 ]. Our observed increase in fibrinogen concentration after 3 months of hormone therapy may indicate temporarily increased pro-coagulant activity.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have observed that despite the negative effects of testosterone therapy on surrogate risks factors of CV disease, these do not translate into a significant effect on CV outcomes (Table 2). Furthermore, no elevated rates of CV deaths have been observed when compared with cisgender men and women at short and medium follow-up (30,35,40,56).…”
Section: Cardiovascular Outcomes In Transgender Menmentioning
confidence: 98%
“…A systematic review and meta-analysis of CV outcomes in transgender people reported few cases of myocardial infarction (MI), stroke, or venous thrombosis; however, the incidence was higher in transgender women compared to transgender men (35,40).…”
Section: Cardiovascular Outcomes In Transgender Womenmentioning
confidence: 99%